2016
DOI: 10.1021/acs.jpcc.6b07181
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lithium Salt in Nanostructured Silica–Polyethylene Glycol Solid Electrolytes for Li-Ion Battery Applications

Abstract: Organic–inorganic hybrid solid electrolytes based on silica–polyethylene glycol PEG(200, 400) with bis­(trifluoromethane)­sulfonimide lithium salt (LiTFSI) or lithium trifluoromethanesulfonate (LiOTf) were synthesized by a sol–gel process. The thermal and structural properties of the materials thus obtained were systematically investigated by a variety of techniques including SEM, TGA-DTA, DSC, FTIR, Raman, and multinuclear (1H, 13C, 7Li) solid-state NMR. Arrehenius behavior was observed for solid hybrid elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 66 publications
0
24
0
Order By: Relevance
“…Interestingly, compared with PIL, CPE samples have higher T g values because of the interaction between the oxygen atoms of PEG800 and the lithium ions. [40] Furthermore, as displayed in Figure 4(c), increasing the content of PEG800 decreases the T g value of CPE samples, which is attributed to that a decrease in lithium salt concentration caused by the increase of PEG800 content will decrease the extent of intermolecular interaction. [41] Figure 4(d) reports the XRD patterns of PEG800, and PIL-PEG800 electrolytes.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Interestingly, compared with PIL, CPE samples have higher T g values because of the interaction between the oxygen atoms of PEG800 and the lithium ions. [40] Furthermore, as displayed in Figure 4(c), increasing the content of PEG800 decreases the T g value of CPE samples, which is attributed to that a decrease in lithium salt concentration caused by the increase of PEG800 content will decrease the extent of intermolecular interaction. [41] Figure 4(d) reports the XRD patterns of PEG800, and PIL-PEG800 electrolytes.…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, it is well established that low lithium salt amount tends to form Li + −polyether interactions instead of Li + ⋅⋅⋅TFSI − complexes ,,. Thus, the increase in the PEG800 amount results in a decrease in the LiTFSI amount in CPEs, making Li + interact with polyether more easily, which subsequently increase mobile ions number, and thereby raise the ionic conductivity ,. Further PEG800 amount increase leads to a drop of ionic conductivity and an increase of E a , which may be attributed to that excess amounts of PEG800 block the ion motion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, this in situ formed silica network markedly suppresses the crystallinity of the material along with improving its mechanical and thermal stability . The collective effect of various factors such as proper synthesis conditions, an optimized stoichiometric ratio of organic and inorganic components and nature of interaction between them decides the structural, morphological, and electrochemical properties of the prepared hybrid electrolytes …”
Section: Introductionmentioning
confidence: 99%
“…Beside the use of molecular solvents, ionic liquids are also used as liquid plasticizers for the study of PEO/Li + salt mixtures . Other literature studies have also been reported regarding the dynamical aspects of EO‐based polymers and their mixtures with various materials and solvent system . However, fewer facts are known regarding the structure and dynamics of these EO‐based polymers in their lithium salt mixtures with molecular solvents.…”
Section: Introductionmentioning
confidence: 99%